Rare Earth Ion Doped Luminescent Materials: A Review of Up/Down Conversion Luminescent Mechanism, Synthesis, and Anti-Counterfeiting Application - Ziyu Chen; Hang Zhu; Jiajie Qian; Zhenxiong Li; Xiameng Hu; Yuao Guo; Yuting Fu; Huazhong Zhu; Wei Nai; Zan Yang; Dan Li; Liling Zhou (Photonics, 2023)
With the rapid development of modern technology and information systems, optical anti-counterfeiting and encryption have recently attracted considerable attention. The demand for optical materials is also constantly increasing, with new requirements proposed for performance and application fields. Currently, rare earth ion doped materials possess a unique electronic layer structure, underfilled 4f5d electronic configuration, rich electronic energy level, and long-life excited state, which can produce a variety of radiation absorption and emission. The distinctive properties of rare earth are beneficial for using in diverse optical output anti-counterfeiting. Design is essential for rare earth ion doped materials with multiple responsiveness and multi-channel optical information anti-counterfeiting in the field of information security. Therefore, this mini review summarizes the luminescent mechanisms, preparation methods, performance characteristics and anti-counterfeiting application of rare earth doped materials. In addition, we discuss some critical challenges in this field, and potential solutions that have been or are being developed to overcome these challenges.